Bone tumors developed in patients with juvenile inflammatory arthritis after anti-TNFα therapy. (6th September 2018) - Chi, Huihui; Teng, Jialin; Yang, Chengde; Su, Yutong
Administration of anti-TNFα agents has become a mainstay in the treatment of chronic inflammatory arthritis such as rheumatoid arthritis (RA) and spondyloarthritis. Adverse events, including infections and allergic reactions, have been reported. Malignancies are rare but potentially life threatening. The existence of bone tumor in those patients is very rare, only five cases of bone tumors were mentioned in juvenile idiopathic arthritis (JIA) in the literature. We describe three patients in whom bone neoplasms developed after years of anti-TNFα therapy for JIA or juvenile ankylosing spondylitis (JAS). One patient developed chondroblastoma, and the other two were diagnosed with osteosarcoma. Rheumatologists should increase their awareness of bone neoplasia in JIA or juvenile ankylosing spondylitis patients after anti-TNFα treatment.